MINAT MASYARAKAT DALAM MENGGUNAKAN PEMBIAYAAN PADA PERBANKAN SYARIAH (Studi Kasus : Rw 02 Nusa Indah Kecamatan Ratu Agung Kota Bengkulu). - Orisa Capriyanti; Ismi Azis; Arista khairunnisa; Agnes yolanda; Beta lorena (Sekolah Tinggi Ilmu Ekonomi Syariah Nahdlatul Ulama Bengkulu, 2020)
This study aims to determine community interest and factors that influence community interest in Rw 02 Nusa Indah, Ratu Agung District, Bengkulu City, this study uses a descriptive qualitative method with data collection techniques collected in the form of words, pictures and not numbers by conducting interviews with several entrepreneurs and communities around Nusa Indah, researchers took 8 respondents, 4 of whom were entrepreneurs in Nusa Indah and 4 were local communities by random sampling. interested in using financing in Sharia Banking because in Syari'ah Banking it uses the principles of Islamic law, the public in using Islamic banking finance avoids usury and the public already knows information about Islamic banking. Factors affecting the community In RW 02 Nusa Indah, Ratu Agung District, Bengkulu City, the community has knowledge of Islamic banking, the community has experience in borrowing from Islamic banks, the community has a social structure capable of using Islamic banking financing, and people get socialization and information about sharia banking. Sharia banking is the right choice for people who want to avoid the sin of usury, for the sake of safety for the afterlife, not a few people who understand religion prefer to do sharia banking transactions.